National interests in Russia’s foreign policy - V. P. Nazarov (Vestnik MGIMO-Universiteta)
The article explores the conceptual landscape surrounding national interests. It posits that the identification, safeguarding, and advancement of national interests serve as the bedrock upon which state policies in the domain of national security are formulated. The article traces the origins, evolution, and contemporary interpretations of national interests. Special emphasis is accorded to interpretations espoused by proponents of the political realism. The author conducts an in-depth examination of Russian perspectives on national interests during the 19th and early 20th centuries, as well as throughout the Soviet era, presenting an original periodization of conceptual approaches within Soviet Russia and the USSR. In addition to its historical inquiry, the article critically assesses the implications of national interests of contemporary Russia’s foreign policy. Through analysis of strategic policy documents, the author discerns instances where policy objectives are conflated with the national interests, diverging from their realization.Given Russia's distinctive geopolitical position and security challenges, the author defines the paramount Russia's national interest – establishing a secure periphery characterized by cooperative relationships with neighboring states and ensuring unimpeded access to global maritime routes.